Fatigue properties of bimetallic steel bar: An experimental and numerical study. (June 2022) - Hua, Jianmin; Wang, Fei; Xue, Xuanyi; Fan, Haifeng; Yan, Wei
Highlights: Effects of strain amplitude on fatigue properties of bimetallic steel bar were investigated. Variation trends of stress–strain properties of bimetallic steel bar were discussed. A numerical simulation method was suggested to quantify fatigue properties of bimetallic steel bar. Abstract: The corrosion of reinforcement has a serious impact on the life cycle service performance of reinforced concrete (RC) structures. To improve the durability, the use of a bimetallic steel bar (BSB) composed of stainless-steel cladding and carbon steel substrate is suggested. Stainless-steel cladding blocks the contact between the carbon steel substrate and the corrosive environment. The low-cycle fatigue properties of the BSBs were investigated. With an increase in the strain amplitude, the peak stress in the stable hysteretic curve of the BSB increased gradually. Different coefficients were selected to clarify the variation trend of the stress, strain, and energy properties. A fatigue model revealing the relationship between the plastic strain range, cycles to failure, and strength loss coefficient was investigated. The effects of nonlinear mechanical properties and inelastic buckling on the low-cycle fatigue properties of the BSB were included in the numerical simulation.